Case reports: Using Good Psychiatric Management (GPM) conceptualizations in the dimensional assessment and treatment of personality disorders - Blay, Martin; Benmakhlouf, Ines; Duarte, Miguel; Perroud, Nader; Greiner, Christian; Charbon, Patrick; Choi-Kain, Lois; Speranza, Mario (Frontiers in Psychiatry, 2023)
Good Psychiatric Management (GPM) is a generalist clinical management approach for borderline personality disorder (BPD) that incorporates common ingredients of good standard care for any psychiatric diagnosis with what works from prevailing specialist psychotherapies. Similar to all validated therapies for BPD, it relies on a specified formulation of the disorders’ symptoms as arising from interpersonal hypersensitivity (IHS), to dynamically describe typical patterns of daily self- and interpersonal issues that drive the instability that defines the general personality dysfunction characteristic of the disorder. Recent adaptations of GPM have been proposed for narcissistic personality disorder and obsessive-compulsive personality disorder, with development of a similar dynamic models for both (intrapsychic coherence model and model of overcontrol). New dimensional models of personality disorder diagnosis have been developed to address limitations of categorical approach, but the incorporation of these models into usage in the delivery of clinical services (where categorical approach remains the most used) is limited. This paper describes an adaptation of GPM to two cases of personality disorder that illustrate the usefulness of GPM models for dynamic representation of complex daily fluctuations in internal psychic coherence and interpersonal functioning. Specialist psychotherapies will never meet the demands of public health needs to treat personality dysfunction, and incorporation of new dimensional models of diagnosis are needed for treatments that can provide a minimal standard of care for providers and patients.